Liberalism and the virtues - MacLean, Jayson R (University of Ottawa (Canada), 2006)
This thesis argues for a new understanding of liberal morality and its relationship to liberal justice. Traditionally, theorists of liberal democracy have relegated the liberal virtues---traits such as tolerance, reasonableness, and fairness---to a secondary role within the theory and practice of liberal justice. Their reasoning for this is clear: the virtues prescribe a vision of the good life, while the aim of the liberal approach to statecraft is to limit government authority over citizens' conceptions of the good. Thus, to give the liberal virtues primacy of place within the theory of justice---and, specifically, within the justification for this theory---would stand in contravention of this basic liberal tenet. The argument of this thesis is that liberal theorists have misrepresented the virtues and that this has caused the neglect of the foundational role which the ideal of civic virtue plays within both the theory and practice of liberal democracy. This argument is advanced through an explication of the theories put forward by contemporary liberal theorists who focus on the import of liberal virtue. Their approaches to virtue are shown to consistently rest on a justification of liberal virtue as an instrumental good for the liberal polity. The claim of this thesis, however, is that the virtues are rightly justified as intrinsic liberal goods. This claim is supported through appeal to insights produced in another branch of philosophy, virtue theory. Similar to their predicament within the political theory of the modern era, the virtues have been downplayed in the field of ethics as well, and only within the past few decades have philosophers begun to reinvestigate the virtues for their distinctive strengths and weaknesses. This thesis argues that the fruits of these investigations prove relevant to liberal theory in that they not only help make a case for the appropriateness of the declaration that the liberal virtues are, in fact, intrinsic goods but also they point to a new approach to liberal morality and, hence, to a new dialogue on the issues of liberal citizenship and liberal civic education.
Keywords: Philosophy.